2013
DOI: 10.1371/journal.pone.0060027
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Tumor Suppressing Function of CACNA2D3 in Esophageal Squamous Cell Carcinoma

Abstract: BackgroundDeletion of 3p is one of the most frequent genetic alterations in esophageal squamous cell carcinoma (ESCC), suggesting the existence of one or more tumor suppressor genes (TSGs) within these regions. In this study, one TSG, CACNA2D3 at 3p21.1, was characterized.MethodsExpression of CACNA2D3 in ESCCs was tested by quantitative real-time PCR and tissue microarray. The mechanism of CACNA2D3 downregulation was investigated by methylation-specific polymerase chain reaction (MS-PCR). The tumor suppressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…Silencing C2ORF40 expression promoted breast cancer cell proliferation, migration and invasion. These are consistent with the findings by Li et al 9,11 that upregulation of C2ORF40 inhibits cell proliferation and invasiveness in ESCC and our bioinformatics analysis of clinical information of breast cancer patients. Our data provided the first biological evidence that C2ORF40 may serve as a tumor suppressor in breast cancers.…”
Section: Methodssupporting
confidence: 93%
“…Silencing C2ORF40 expression promoted breast cancer cell proliferation, migration and invasion. These are consistent with the findings by Li et al 9,11 that upregulation of C2ORF40 inhibits cell proliferation and invasiveness in ESCC and our bioinformatics analysis of clinical information of breast cancer patients. Our data provided the first biological evidence that C2ORF40 may serve as a tumor suppressor in breast cancers.…”
Section: Methodssupporting
confidence: 93%
“…Therefore, it is crucial to identify tumor molecular markers that are predictive of survival and metastasis and can identify ESCC patients who may benefit from surgical resection. Recently, several genes that are associated with ESCC metastasis have been identified, including Gadd45G [10], glioma-associated oncogene homolog 1 [11], lysine-specific demethylase 1 [12], maspin [13], PLCE1 [14], and CACNA2D3 [15]. These studies have indicated that specific genes may contribute to the metastasis of ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C2ORF40 has been demonstrated to be chemosensitive to 5-fluorouracil and cisplatin (23,24). Previous research by the present authors demonstrated that C2ORF40 is a candidate tumor suppressor gene and an independent prognostic factor in ESCC, and C2ORF40 gene overexpression inhibits tumor cell proliferation and invasion in ESCC (25)(26)(27)(28)(29). Notably, additional bioinformatics analysis indicated that pro-C2ORF40 protein was a secreted protein with a signal peptide.…”
Section: Introductionmentioning
confidence: 63%